Effects of Curcumin Treatment in a Diabetic Neuropathic Pain Model of Rats: Involvement of c-Jun N-Terminal Kinase Located in the Astrocytes and Neurons of the Dorsal Root Ganglion. (19th January 2021) - Park, Hanwool; Lee, Jong-Hyuk; Sim, Ji Hoon; Park, Jihoon; Choi, Seong-Soo; Leem, Jeong Gil
Abstract : Curcumin (diferuloylmethane) is a major component of turmeric, which is isolated from the rhizomes of Curcuma longa L. from the family Zingiberaceae. It is used as a dietary pigment for curry and in traditional Indian medicine for its anti-inflammatory and attenuating pain effects. This study aimed to evaluate the beneficial effects of curcumin in a rat model of diabetic neuropathic pain. Additionally, we investigated the involvement of the phosphorylated form of c-Jun N-terminal kinase (pJNK) located in the neurons and astrocytes of the dorsal root ganglion (DRG). To induce diabetic neuropathic pain in rats, 50 mg/kg of streptozotocin (STZ) was intraperitoneally injected. After 4 weeks, rats were administered the vehicle, 10 mg/kg/day curcumin, or 50 mg/kg/day curcumin orally for 4 consecutive weeks. One day after the final drug administration, we performed behavioral tests to measure responses of rats to mechanical, heat, cold, and acetone-induced cold stimuli. After behavioral tests, pJNK expression in the DRG was evaluated using western blot assay and immunohistochemistry. Curcumin treatment for 4 consecutive weeks in STZ-induced diabetic neuropathic pain rats improved behavioral responses to mechanical, cold, and thermal stimuli. Increased pJNK expression in the astrocytes and neurons of the DRG in STZ-induced diabetic neuropathic pain rats was reduced by curcumin treatment for 4 consecutive weeks. We suggest that curcumin can be an option for the treatment of diabetes-related neuropathic pain, and one of the mechanisms that underlie the action of curcumin may involve pJNK expression in the astrocytes and neurons of the DRG.